Attitudes of physics teachers towards the use of electronic evaluation tools in designing the performance tasks in the administration of Sebia’s education - Zabbani, Munjiyah Ali (Journal of Educational and Psychological Sciences, 2022)
The study aimed to reveal the attitudes of physics teachers towards the use of electronic evaluation tools in designing performance tasks in the Sebaya Education Department. In order to achieve the objectives of the study, the study applied the descriptive analytical method. The study sample consisted of (85) male and female teachers. The study also used the questionnaire as a main tool in data collection. The most important findings of the study are that the most important ways to develop the attitudes of physics teachers towards the use of electronic assessment tools in the design of performance tasks are to educate and educate the student about the importance of distance education, and to provide free Internet services to facilitate the application of electronic assessment tools for each teacher and student who needs them. There are statistically significant differences between the average estimates of the sample members about the attitudes of physics teachers towards the use of electronic evaluation tools in designing the performance tasks due to gender. Based on the findings of the study, the study recommended the necessity of employing electronic evaluation tools in designing the performance tasks.
Keywords: electronic evaluation tools; design of performance tasks; physics teachers